2018
DOI: 10.1177/1524839918757755
|View full text |Cite|
|
Sign up to set email alerts
|

The CHAMPIONS NETWork: Training Chicago High School Students as Health Advocates to Improve Health Equity

Abstract: In Chicago, major disparities exist across ethnic groups, income levels, and education levels for common chronic conditions and access to care. Concurrently, many of Chicago's youth are unemployed, and the number of minorities pursuing health professions is low. In an effort to eliminate this health equity gap, the University of Illinois at Chicago convened a community-university-hospital partnership to implement the CHAMPIONS NETWork (Community Health And eMPowerment through Integration Of Neighborhood-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Selected students from prioritized high schools in underserved areas complete a 6-week paid summer program. Since the program began in Summer 2016, the health advocacy training has been completed through didactic and hands-on curriculum (Heinert, Del Rios, et al, 2019) and has shown increased student empowerment (Heinert, Kowalski, et al, 2019).…”
Section: Career Developmentmentioning
confidence: 99%
“…Selected students from prioritized high schools in underserved areas complete a 6-week paid summer program. Since the program began in Summer 2016, the health advocacy training has been completed through didactic and hands-on curriculum (Heinert, Del Rios, et al, 2019) and has shown increased student empowerment (Heinert, Kowalski, et al, 2019).…”
Section: Career Developmentmentioning
confidence: 99%
“…HPP is proud to announce that “The CHAMPIONS NETWork: Training Chicago high school students as health advocates to improve health equity in their communities” (Heinert et al, 2019) has been selected as our 2019 Paper of the Year, recipient of the Sarah Mazelis Award. Dr. Sara Wieseneck Heinert, University of Chicago at Illinois, led the author team that included Marina Del Rios, Arjun Arya, Ramin Amirsoltani, Nasseef Quasim, Lisa Gehm, Natalia Suarez, and Terry Vanden Hoek.…”
Section: The Health Promotion Practice 2019 Paper Of the Year: The Samentioning
confidence: 99%
“…By engaging students to become part of the health care team, the CHAMPIONS NETWork can improve the health of Chicago’s most underserved communities while empowering students in a novel way and building a pathway that equips them to join the health care workforce. (Heinert et al, 2019, p. 59)…”
Section: The Health Promotion Practice 2019 Paper Of the Year: The Samentioning
confidence: 99%
“…The collection is available online (http://bit.ly/30ptviy) and will be published in our November 2019 issue. Combined with recent HPP articles on LGBT-inclusive teen pregnancy prevention (Boyce, Travers, Rothbart, Santiago, & Bedell, 2018), the Icelandic model of adolescent substance use prevention (Kristjansson et al, 2019), school-based gun safety education (Holly Porter, Kamienski, & Lim, 2019), and engaging youth as health equity advocates (Heinert et al, 2019; Lane, Porter, Hecht, Harris, & Zoellner, 2019), a richly textured picture emerges of the vibrant and life-affirming possibilities that all children need and deserve.…”
Section: What You’ll Find In This Issuementioning
confidence: 99%